MicroARPES and nanoARPES at diffraction‐limited light sources: opportunities and performance gains. (1st September 2014) - Rotenberg, Eli; Bostwick, Aaron
<x xml:space="preserve">Abstract</x> The scientific opportunities for microARPES and nanoARPES techniques are discussed, and the benefits to these techniques at diffraction‐limited light sources are presented, in particular the impact on spectromicroscopic ARPES (angle‐resolved photoemission spectroscopy) of upgrading the Advanced Light Source to diffraction‐limited performance. The most important consideration is whether the space‐charge broadening, impacting the energy and momentum resolution, will limit the possible benefits for ARPES. Calculations of energy broadening due to space‐charge effects will be presented over a wide range of parameters, and optimum conditions for ARPES will be discussed. The conclusion is that spectromicroscopic ARPES will greatly benefit from the advent of diffraction‐limited light sources; space‐charge broadening effects will not be a limiting factor.